Development of Aesthetic Perception in 4-8-Year-Old Children Using the Method of Observing Artworks - Jurga Sidabrienė (Acta Paedagogica Vilnensia)
In the research on cultural education activities in European countries (2021), questions are raised about whether digital development and improved children’s access to cultural resources inherently contribute to a more successful development of children’s aesthetic perception. International studies on children’s aesthetic education (Savva, Acer, Beck, Kim, Denac, Bergman, Yi-Huang Shih Ching, etc.) highlight children’s participation in observing works of art as a condition for promoting children’s aesthetic perception. However, attention is drawn to the insufficient art competencies of early childhood educators in the context of exploring works of art. This article aims to demonstrate that the method of observing works of art can be an effective means of fostering children‘s aesthetic perception, provided that educators seek to acquire sufficient knowledge and competencies for the application of the art observation method. For this purpose, a literature analysis method was chosen for the study: based on insights provided by foreign and Lithuanian researchers, the article presents the structure of the art observation/research method, distinguishing visual and aesthetic components of the artwork. It also introduces recommended artists from foreign studies, identifies the most effective ways and forms of presenting artworks for the development of children’s aesthetic perception, and reviews the contexts and practices of applying the art observation method in international studies for children aged 4–8.